A Systematic Review Involving Actively Practising Adult Branch Nurses Experiences & Attitudes towards Mental Health Illness - Brighton, Emily (2014)
Abstract Aims and Objectives: To record and synthesis the findings of studies examining the attitudes and experiences of qualified adult nurses working in a general hospital, with psychiatric clients. Background: Since the closure of the asylums, individuals diagnosed with a mental health disorder have been subject to high levels of stigma from various members of the general public. This has also translated into healthcare, with studies showing that qualified adult branch nurses also have stigmatised ideas against individuals diagnosed with a mental health disorder, preventing them from receiving high quality care. This systematic review has been undertaken to explore the attitudes and experiences qualified adult nurses experience when caring for a client diagnosed with a psychiatric disorder. Design: A system of meta-synthesised findings were established, grouped by similarity in meaning and common factors, to produce themes across a variety of published papers. Results: Nurses experienced both positive and negative attitudes, with a large amount of negative attitudes focusing on lack of education. Nurses experiencing education within mental health reported more positive experiences. Conclusions: Nurses require additional support and education when caring for psychiatric clients, to receive a good experience and deliver high quality care to the psychiatric clients.